Analisis Peran Badan Kepegawaian, Pendidikan dan Pelatihan Daerah (BKPPD) dalam Pengembangan Karir Pegawai Negeri Sipil di Lingkungan Kabupaten Magelang - Yuni Kurniasih; Daifullah, Bagas (Universitas Widya Mataram, 2024)
The number of Civil Servants in Magelang Regency as of 2020 is 6,932 people. Apart from that, the influx of additional personnel is 2,213 Government Employees with Work Agreements (PPPK). Based on this data, it creates an opportunity for BKPPD Magelang Regency to hold a Career Development program for State Civil Apparatus to be able to improve employee performance by filling strategic positions in the government such as functional positions and other positions and ranks. This research aims to explain and analyze the role of the Personnel, Education and Training Agency (BKPPD) in the career development of civil servants in the Magelang Regency environment. The research was carried out using qualitative research methods and was based on Jim Ife's role theory, namely the facilitative role and technical role and used purposive sampling and simple random sampling informant selection techniques. The research results show that the steps taken by the BKPPD of Magelang Regency, namely as a facilitator, include a functional position development program and structuring of ASN starting from increasing capabilities through education and training to improving services through service innovation such as providing administrative services which are not only implemented on the table but are already implemented. innovate with technological developments and are supported by technical activities through self-development activities such as through education and training activities which aim to shape the character of ASN so that they have the spirit of being a public servant while at the same time enhancing the integrity and professionalism of ASN's performance. Keywords: BKPPD Magelang Regency; Role; Civil Servant Career Development.